Astrid Lindgren oggi. Spunti per una riflessione - Franco Cambi (Firenze University Press, 2009)
The Author does a study in deep about the charming work of Astrid Lindgren. Her books rapresent a widening of social childhood, and we can find some marks of fantastic mind and unconventional behaviour in them. The Author underlines the actuality of Lindgren's literature.